Potential of pyrethroid insecticides and plant extracts on fecundity and egg viability of Tribolium castaneum (Herbst) - Jilani, SNK; Islam, W; Mondal, KAMSH (Journal of Bio-Science, 2012)
Context: Sythetic pyrethroid and two botanical may reduce the fecundity and egg viability of red flour beetle, Tribolium castaneum (Herbst) and can be used in grain protection. Objective: To determine the effect of cypermethrin, fenitrothion, Murraya paniculata L. and Jatropha gossypifolia L. plant extracts on fecundity and egg viability of T castaneum. Materials and Methods: Newly hatched T. castaneum larvae were kept in a petridish containing 30 g either fresh or treated flour separately. After pupation the pupae were sieved and sexed by microscopic examination and kept separately for adult emergence. Twenty five pairs (1?: 1?) adults were paired from treated and one pair from untreated media and placed in a glass vial containing 2 g of food either treated or untreated for oviposition in an incubator at 30 ± 0.5°C. Eggs were collected and counted after every three days over a period of 45 days. The eggs laid by the first 15 pairs from each treatment were collected from the experimental vials and kept in separate petridish for hatching. Eggs were regularly observed with a microscope and hatched larvae were counted. Results: The females of all treated media laid less number of eggs than the untreated females. Both insecticides and botanicals affected oviposition significantly (P<0.001) at all doses levels. All the treatments of both the insecticides and botanicals significantly (P < 0.001) reduced the fertility of eggs laid by T. castaneum females in comparison to those of the control. Conclusion: The plant extracts of kamini and jamalgota can effectively reduced the fecundity and egg viability against stored product insect pests with low mamalian toxicity. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13007 J. bio-sci. 19 95-97, 2011